Potensi Tumbuhan Lokal Desa Meranti Sebagai Konten dan Media Pembelajaran Berbasis Kearifan Lokal pada Materi Kimia - Tangio, Julhim S.; Utina, Ramli; Yusuf, Frida Maryati; Kunusa, Wiwin Rewini; Karim, Cecy Rahma; Arviani, Arviani (Universitas Negeri Gorontalo, 2023)
Chemistry lessons are subject matter whose concepts are often found in students' daily lives, but many teachers have not been able to integrate the phenomena of chemistry and the potential of local plants into learning. The purpose of this research is to describe the potential of local plants as content and learning media based on local wisdom. The results of the study show that several types of plants found in the tourist area of Meranti Village can be used as chemistry learning content and media. These plants, namely belimbing wuluh flower, softwood flower and red spinach can be used as natural indicators instead of synthesis indicators for testing acid and alkaline solutions and Sago from sago trees is developed as a learning medium for molecular shape models